2021
DOI: 10.1097/mnm.0000000000001465
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-head comparison between 68Ga-PSMA and 18F-FDG-PET/CT in lymphomas: a preliminary analysis

Abstract: Purpose Isolated case reports mention the uptake of radiolabeled PSMA in lymphoma. However, it is not clear if the intensity of 68Ga-PSMA expression varies among different histological subtypes or if it correlates with 18F-FDG uptake. This study compared both tracers in patients with diverse lymphoma subtypes. Methods Ten patients with biopsy-proven-lymphoma underwent 18F-FDG and 68Ga-PSMA-PET/CT (maximum time interval: 6 days). Lymphoma subtypes included Hodgkin’s lymphoma (HL, three patients) and aggressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In the past, a needle biopsy was the standard method to identify whether extra-prostate tissue involvement was present, while it may lead to some complications (i.e., bleeding and infection). Recently, de Souza et al pointed out that lymphoma may present as PSMA uptake after reviewing the data of 10 patients with different histological subtypes of lymphomas, and they subsequently found that the intensity of PSMA uptake was generally lower than FDG ( 11 ). Furthermore, several published case reports have also found that the PSMA expression of lymphoma was extremely low, or even had no expression ( 12 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the past, a needle biopsy was the standard method to identify whether extra-prostate tissue involvement was present, while it may lead to some complications (i.e., bleeding and infection). Recently, de Souza et al pointed out that lymphoma may present as PSMA uptake after reviewing the data of 10 patients with different histological subtypes of lymphomas, and they subsequently found that the intensity of PSMA uptake was generally lower than FDG ( 11 ). Furthermore, several published case reports have also found that the PSMA expression of lymphoma was extremely low, or even had no expression ( 12 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Only one other report identified in the literature showed a patient with a history of diffuse large B-cell lymphoma to be positive on PSMA PET scan. 8 Given the increasing availability of the PSMA PET scan after Food and Drug Administration approval in December 2020 because of its superiority to conventional imaging in detecting prostate cancer metastases, 9,10 it is important to be aware of the landscape of other diseases, such as lymphoma, which this seemingly specific scan can detect. This case emphasizes the importance of confirmatory biopsy when atypical findings occur on a 68 Ga-PSMA PET scan.…”
mentioning
confidence: 99%
“…To the best of our knowledge, this is the first case of a previously unknown high-grade lymphoma diagnosed via PSMA PET/CT. Only one other report identified in the literature showed a patient with a history of diffuse large B-cell lymphoma to be positive on PSMA PET scan 8 . Given the increasing availability of the PSMA PET scan after Food and Drug Administration approval in December 2020 because of its superiority to conventional imaging in detecting prostate cancer metastases, 9,10 it is important to be aware of the landscape of other diseases, such as lymphoma, which this seemingly specific scan can detect.…”
mentioning
confidence: 99%
“…14,15 Furthermore, lutetium-177-labeled PSMA shows promising results for successful endoradiotherapeutic treatment of metastatic hormone-sensitive and castration-resistant prostate cancer with survival benefits. 12,13 Interestingly, PSMA PET avidity has also been reported to occur in nonprostatic malignancies to include glioblastoma, 16 hematolymphoid malignancies, 17,18 thyroid cancer, 19 and HCC. [20][21][22][23][24] For liver cancer, PSMA-targeted radioligands may have significant clinical implications as diagnostic imaging and management of HCC in cirrhotic patients remain challenging.…”
mentioning
confidence: 99%